A review on the sinking mechanisms for oil and successful response technologies. (November 2020) - Jacketti, Mary; Beegle-Krause, C.J.; Englehardt, James D.
Abstract: A rise in the shipping of heavier hydrocarbon products increases the potential for an oil to sink after a spill. Further, sunken oil is difficult to locate and recover, and appropriate response technologies depend on the sinking mechanism. In this review, principal sinking mechanisms for oil are described and appropriate response technologies are suggested. Then, models appropriate for tracking sunken oil are compared. Oil may sink as burn residue, microscopic oil-particle aggregates (OPAs) or macroscopic oil-sediment mixtures (OSMs), marine oil snow during a MOSSFA event, or due to its high density. The most common mechanism is by sediment entrainment, and in such scenarios manual recovery has been reported as a successful response option. Among oil tracking models, trajectory models and Bayesian oil search models are compared for sunken oil capabilities. Many oil spill models require hydrodynamic inputs, whereas Bayesian models infer parameters based on available field concentration and bathymetric data. Highlights: Oil may sink due to its high density or by mechanisms that make the oil denser. Processes include sediment interaction and the formation of MOSSFA and burn residue. Successful detection and recovery depend on the specific sinking mechanism. Advancements in sunken oil spill models are being made to assist during response.